2016
DOI: 10.1080/15287394.2016.1143901
|View full text |Cite
|
Sign up to set email alerts
|

The association of serumtrans-nonachlor levels with atherosclerosis

Abstract: Recent epidemiological studies suggest a strong association between exposure to environmental contaminants, including organochlorine (OC) insecticides or their metabolites, and development of pathologies, such as atherosclerosis, in which oxidative stress plays a significant etiological role. Biomarkers of systemic oxidative stress have the potential to link production of reactive oxygen species (ROS), which are formed as a result of exposure to xenobiotic toxicants, and underlying pathophysiological states. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…β-HCH exhibits characteristics of both an endocrine disrupting chemical and an activator of AhR signaling, thereby facilitating the development of oxidative stress, as well as has the capacity to cause DNA damage through H2AX phosphorylation . Similarly, elevated levels of transnonachlor have been linked to clinical manifestations of atherosclerosis, compromised glycemic control, and impaired beta cell function . Exposure to OC mixtures in mice has also shown to be able to intensify oxidative and inflammatory stressors in the heart to overwhelm protective mechanisms allowing for adverse cardiac remodeling …”
Section: Discussionmentioning
confidence: 99%
“…β-HCH exhibits characteristics of both an endocrine disrupting chemical and an activator of AhR signaling, thereby facilitating the development of oxidative stress, as well as has the capacity to cause DNA damage through H2AX phosphorylation . Similarly, elevated levels of transnonachlor have been linked to clinical manifestations of atherosclerosis, compromised glycemic control, and impaired beta cell function . Exposure to OC mixtures in mice has also shown to be able to intensify oxidative and inflammatory stressors in the heart to overwhelm protective mechanisms allowing for adverse cardiac remodeling …”
Section: Discussionmentioning
confidence: 99%
“…The result of this study seems similar to that of recent studies. A previous study reported that OC pesticides were related to the higher prevalence of peripheral artery diseases [8] and that elevated serum levels of OC pesticides were associated with the risk of atherosclerosis [9]. Meanwhile, other researchers found contrasting results wherein lower mortality from coronary artery disease was seen with higher exposure to herbicides [10]; and no significant relationship was reported between OC pesticides, polychlorinated biphenyls, and CIMT [4].…”
Section: Plos Onementioning
confidence: 99%
“…With the recently growing concern and interest for environmental chemicals, pesticide exposure is emerging as a risk factor for atherosclerosis [4,5]. Although pesticide exposure has been linked with cardiovascular diseases [6,7] and serum levels of organochlorine (OC) pesticides are associated with several forms of atherosclerosis [8,9], the association between pesticide exposure and atherosclerosis is unclear. Moreover, previous studies on this issue have not provided consistent results [10], prompting the need for further investigation.…”
Section: Introductionmentioning
confidence: 99%